2004
DOI: 10.1007/s00394-004-0450-x
|View full text |Cite
|
Sign up to set email alerts
|

Green tea supplementation ameliorates insulin resistance and increases glucose transporter IV content in a fructose-fed rat model

Abstract: Based on these results, we suggest that the amelioration of insulin resistance by green tea is associated with the increased expression of GLUT IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
106
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(115 citation statements)
references
References 32 publications
6
106
0
3
Order By: Relevance
“…Accordingly, the doses (5-100 M) of EGCG (the effective dose of this study is in the range of 20 -100 M) or other tea catechins generally used in this study that are compatible with the goal of helping to regulate the initiation and progression of obesity and diabetes (27) were a little bit higher, but might be acceptable for the physiological effect of EGCG in animals. This is indirectly supported by the evidence that green tea extract given to rats by oral administration at a dosage of 0.5 g/100 ml water, which contained ϳ2,183 M EGCG, could within 12 wk improve insulin sensitivity in rats and that green tea extract containing 327 M EGCG enhanced glucose uptake in rat adipocytes in vitro (53).…”
Section: Discussionsupporting
confidence: 56%
“…Accordingly, the doses (5-100 M) of EGCG (the effective dose of this study is in the range of 20 -100 M) or other tea catechins generally used in this study that are compatible with the goal of helping to regulate the initiation and progression of obesity and diabetes (27) were a little bit higher, but might be acceptable for the physiological effect of EGCG in animals. This is indirectly supported by the evidence that green tea extract given to rats by oral administration at a dosage of 0.5 g/100 ml water, which contained ϳ2,183 M EGCG, could within 12 wk improve insulin sensitivity in rats and that green tea extract containing 327 M EGCG enhanced glucose uptake in rat adipocytes in vitro (53).…”
Section: Discussionsupporting
confidence: 56%
“…Although (Ϫ)-catechin displays different effects on the regulation of adiponectin expression from the major green tea polyphenols, it would be worthwhile in a further in vivo study to explore whether the effect of (Ϫ)-catechin on adiponectin gene expression in our in vitro study is related to the mechanism by which green tea extracts exert their antidiabetic (26) and antiobesity (16) actions in animals.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that daily supplementation of 0.5 g of green tea for 12 weeks could reduce fasting plasma glucose levels, insulin, triglyceride, and free fatty acids in Sprague-Dawley rats. 49,50 Islam et al reported that green tea intake of 23 g per day could increase serum insulin concentration in rats, and higher consumption of green tea can be beneficial for normal human subjects with hyperlipidemia. 51 Therefore, certain doses of green tea were beneficial for diabetes prevention.…”
Section: Discussionmentioning
confidence: 99%